(untitled) (Bangladesh Journal of Anatomy, 2015)
Context: Examination of bone is important for identification of sex of an individual. The present study was planned to collect data regarding sagittal length of human dry ossified second cervical vertebrae and to find out possible variations in male and female. Materials & Methods: A cross-sectional analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The study materials consist of 156 human dry ossified second cervical vertebrae of unknown sex. The study samples were distributed in male and female sex groups by discriminant function analysis technique. Results: Among 156 vertebrae 55.77% was male and 44.23% was female. The mean (±SD) sagittal length of second cervical vertebrae was greater in male than that of female (P<0.001). Conclusion: Sagittal length of second cervical vertebra was greater in male compared to female. The differences in length can be useful in sex differentiation. DOI: http://dx.doi.org/10.3329/bja.v12i1.22610 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 07-10